Isu-isu Pembelajaran Bahasa dan Sastra Indonesia dengan Pendekatan Kooperatif - Rohana, Rohana (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
In reality, especially in the subjects of Indonesian, learning activities are still carried out in the classical style. Learning is more emphasis on models that are colored by lecturing and teacher-centre. As a result, students are being less involved in in learning activity. Leaning a language rests on the development of students ability to use language as a means of delivering a message / meaning for many language purposes . The aims of learning a language are the ability in mastering listening, speaking, reading and writing. Those skills must be achieved meaningfuly by students. Learning Indonesian language and literature is directed to improve students ability to communicate, both orally and writen. Storytelling in pair, type of cooperative learning in pair, combines reading, writing, listening andspeaking. Therefore the type of cooperative learning in storytelling in pair is suitable for learning Indonesian.